1939
DOI: 10.1037/h0058757
|View full text |Cite
|
Sign up to set email alerts
|

Auditory induction of an abnormal pattern of behavior in rats.

Abstract: Functional disturbances in animal behavior have as yet been little investigated. Nevertheless, they offer experimental possibilities of considerable significance for the study of processes underlying aberrant human behavior. In the pioneer studies of Pavlov (4, 5), neurotic behavior appeared when the animal was presented with a situation which heavily taxed his capacities for discrimination. It consisted of nervousness and emotional disturbances accompanied by the loss of previously acquired conditioned reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

1940
1940
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 2 publications
4
26
0
Order By: Relevance
“…and Watson (1939) have shown that both waltzing and epilepsy (convulsive reaction produced by jingling of keys) in mice are transmitted as a Mendelian recessive trait. A similar convulsive reaction to auditory stimulation in rats has been reported by Maier (1939), Morgan and Morgan (1939), Humphrey and Marcuse (1939), Hall (1940), Bayroff (1940) and Maier and Glaser (1940). The latter suggested that the reaction in rats as in mice was probably hereditarily determined.…”
supporting
confidence: 82%
“…and Watson (1939) have shown that both waltzing and epilepsy (convulsive reaction produced by jingling of keys) in mice are transmitted as a Mendelian recessive trait. A similar convulsive reaction to auditory stimulation in rats has been reported by Maier (1939), Morgan and Morgan (1939), Humphrey and Marcuse (1939), Hall (1940), Bayroff (1940) and Maier and Glaser (1940). The latter suggested that the reaction in rats as in mice was probably hereditarily determined.…”
supporting
confidence: 82%
“…Genetic reflex epilepsy (GRE), which was first described by Morgan and Morgan (1939) [1] , is a type of idiopathic epilepsy in which a stimulus of any sensory modality evokes paroxysmal manifestations only in genetically predisposed subjects. This may occur in humans and animals: the epileptic manifestations are similar among various species, and range from a simple paroxysmal electrical discharge to generalized seizures (see [2] ).…”
Section: Introductionmentioning
confidence: 99%
“…It is relevant to consider the similarities and differences which this case shows with the audiogenic fits in rats investigated by many workers (Maier, 1939;Morgan and Morgan, 1939;Maier and Glaser, 1940;Lindsley and others, 1942). In certain strains of rats, though not carried as a simple mendelian dominant, a susceptibility to abnormal behaviour culminating in convulsions is found as a response to high-pitched sounds (whistle, keyjingling, etc.).…”
Section: Discussionmentioning
confidence: 65%